2019
DOI: 10.1108/ijhma-09-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Housing features and rent: estimating the microstructures of rental housing

Abstract: Purpose While consumers did not previously have information on detailed housing features via traditional media, such as magazines, nowadays, due to the progress in information technology, they can access detailed information on various housing features via housing information websites. Therefore, detailed housing features may affect current rents to some extent. This paper aims to identify the effects of detailed housing features on rent and on omitted variable bias in Tokyo, Japan. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…A prior research study regarding rent prices of housing examined utilitarian as well as hedonic features of the house. Findings revealed that omitting hedonic attributes from the house description caused a biased perception of the utilitarian features listed (Nishi et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A prior research study regarding rent prices of housing examined utilitarian as well as hedonic features of the house. Findings revealed that omitting hedonic attributes from the house description caused a biased perception of the utilitarian features listed (Nishi et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Shimizu [11] demonstrates that the environment surrounding housing is important in the case where house prices are determined by building use conditions and the characteristics of neighboring residents and suggests that in the case such variables are not taken into consideration and the estimated statistics of the hedonic function lack robustness. Nishi et al [8] also show that there is a similar problem with estimated statistics when housing equipment is not taken into consideration. Fuerst and Shimizu [13] show that in the new condominium market in Tokyo, the offered value for highly novel functionality such as environmental performance differs greatly when taking the household's annual income into account.…”
Section: Empirical Analysis: Data and Estimation Model 21 Literaturementioning
confidence: 99%
“…As for variable selection in the estimation of hedonic functions in Tokyo's rental housing market, Nishi et al [8] have conducted an exhaustive survey of the previous research. Nishi et al [8] pointed that the housing amenities used in hedonic analyses are categorized as "location or accessibility,""housing features," and "site advantages." This paper is focused on housing features, because they can be reflected in the rent due to the technological progress in the information systems and supply management.…”
Section: Empirical Analysis: Data and Estimation Model 21 Literaturementioning
confidence: 99%
See 2 more Smart Citations